Consolidating Germany's Russia policy: Refine existing approaches and clarify trade-offs - Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2023)
Climate policy in the European Union (EU) and Germany changed significantly with the adoption of net-zero emissions targets. A key new development is the growing importance of carbon management. The umbrella term includes not only the capture and storage of CO2 (carbon capture and storage, CCS), but also CO2 capture and utilisation (carbon capture and utilisation, CCU) as well as the removal of CO2 from the atmosphere (carbon dioxide removal, CDR). It is important to provide clarity when differentiating between these approaches and identifying their relation to so-called residual emissions and hard-to-abate emissions. This is particularly important because it will determine the overall ambition of climate policy as well as shape future policy designs and their distributional impacts. Current policy and legislative processes should ensure that carbon management does not delay the phase-out of fossil fuels. New policy initiatives present an opportunity to actively shape the interface between ambitious climate and industrial policy.The "Zeitenwende" in international politics implies a need to improve strategic thinking and better prepare for future challenges. Germany is already doing so by drafting strategic documents on national security and relations with China. With respect to Russia, a similar approach suggests itself. First, because Russia's aggression against Ukraine has significantly worsened the situation in Europe and beyond for the foreseeable future. Second, because the conception of a Russia policy based on the principles declared since 2022 offers an opportunity to correct previous mistakes and transform measures that have emerged from a crisis situation into long-term policy.
Keywords: 320; "Zeitenwende"; Germany's Russia policy; NATO; Ukraine; European Union (EU); USA; China; "Expanding Cooperation with Civil Society in the Eastern Partnership Countries and Russia" (ÖPR); energy policy